Trickle-Bed Bioreactors for Acetogenic H2/CO2 Conversion - Steger, Franziska; Ergal, İpek and Daubek, Armin and Loibl, Nadine and Rachbauer, Lydia and Fuchs, Werner and Rittmann, Simon K.-M. R. and Bochmann, Günther (Frontiers in Energy Research, 2022)
Acetic acid is an essential industrial building block and can be produced by gas fermentation with acetogenic bacteria from molecular hydrogen (H2) and carbon dioxide (CO2). However, low specific growth rates and low mass transfer of gaseous substrates into liquid media are the main challenges in gas fermentation of autotrophic microbes. Trickle-bed bioreactors (TBs) have an enhanced gas-to-liquid mass transfer and cells remain in the system by forming a biofilm on the carriers. So far, TBs have been intensively investigated for bio-methanation processes, whereas studies for their use in acetic acid production are rare. In this study, we evaluated trickle-bed systems for acetic acid production from H2 and CO2 with mixed culture. High maximum acetic acid concentration of 40.84 g L-1 was reached. The main families that have been identified in the microbial community analysis were Peptococcaceae, Ruminococcaceae, Planococcaceae, Enterobacteriaceae, Clostridiaceae, Lachnospiraceae, Dysgonomonadaceae and Tannerellaceae. We conclude that a TB is a viable solution for conversion of H2/CO2 to acetate using an anaerobic enrichment culture.